1995
DOI: 10.2175/106143095x131475
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biodegradation of carbon tetrachloride by the supplement of substrate and mineral ions under anaerobic condition

Abstract: The effect of substrate and mineral elements on the anaerobic bioremediation of carbon tetrachloride (CT) was investigated by introducing different substrates and mineral elements into the microbial communities. Glucose, acetate, and humic acid were used as carbon and energy sources for microbial use, ferrous ion was used as the reducing agent, and nitrate was used as the electron acceptor.Experimental results showed that the addition of substrates and mineral ions could enhance the biotransformation efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…There are several mechanisms for the environmental degradation of CCl4 including (a) hydrolysis (1,2); (b) abiotic reductive dehalogenation to CHCl3, which occurs in the presence of iron under anaerobic and aerobic conditions (3,4); and (c) biologically mediated fortuitous reductive dehalogenation by methanogenic bacteria (5,6), sulfate-reducing bacteria (7), or denitrifying bacteria (7)(8)(9)(10)(11)(12). While many halocarbons, including TCA, can be microbially degraded under aerobic conditions as shown by laboratory (13)(14)(15)(16)(17)(18)(19) and field (20)(21)(22)(23) experiments, there are many studies that conclude that microbially mediated aerobic degradation of perchlorinated compounds, such as CCl4, does not occur (18,20,22,23).…”
Section: Introductionmentioning
confidence: 99%
“…There are several mechanisms for the environmental degradation of CCl4 including (a) hydrolysis (1,2); (b) abiotic reductive dehalogenation to CHCl3, which occurs in the presence of iron under anaerobic and aerobic conditions (3,4); and (c) biologically mediated fortuitous reductive dehalogenation by methanogenic bacteria (5,6), sulfate-reducing bacteria (7), or denitrifying bacteria (7)(8)(9)(10)(11)(12). While many halocarbons, including TCA, can be microbially degraded under aerobic conditions as shown by laboratory (13)(14)(15)(16)(17)(18)(19) and field (20)(21)(22)(23) experiments, there are many studies that conclude that microbially mediated aerobic degradation of perchlorinated compounds, such as CCl4, does not occur (18,20,22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Reductive dechlorination of chlorinated hydrocarbons has been observed in both natural and laboratory reducing environments (DiStefano et al, 1991;Gibson and Sewell, 1992;Doong and Wu, 1995). The reductive dechlorination requires an electron donor produced by a transfer of electron from an organic substrate to chlorinated hydrocarbons and the addition of external carbon and energy sources is necessary for the dechlorination of chlorinated hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced in-situ biodegradation of highly chlorinated hydrocarbons is of particular interest owing to their persistences and reported health risks (Federal Register, 1989). Recent studies have demonstrated that heavily chlorinated hydrocarbons can be fortuitously biotransformed under denitrification (Criddle et al, 1990;Semprini et al, 1992;Tatara et al, 1993;Bybas et al, 1995), sulfate-reducing (Bagley and Gossett, 1990;DiStefano et al, 1992;Doong and Wu, 1995b), and methanogenic conditions (Bouwer and Wright, 1988;Gibson and Sewell, 1992;DeBruin et al, 1992) into less chlorinated compounds that are more biodegradable. Rates of transformation are generally faster under more reducing conditions.…”
Section: Introductionmentioning
confidence: 99%